95.0k views
15 votes
Let g(x) = 3(x - 6)^2 + 1. Find the range of $g$.

User Esparver
by
4.5k points

1 Answer

10 votes

Answer:

[1,∞)

Explanation:

Let's try to plug in some numbers.

When solving a problem fo range, the best place to start is where you can let the (x - b) part = 0.

This is what I mean

3(x-6)² + 1

Let x = 6

3(0)² + 1 = 1

Look how we have a 0 inside the parentheses.

That's what I mean.

Now let's try using terms smaller than 6.

Now, let's try plugging in 5

3(-1)² + 1 = 4

Now try plugging in 4

3(-2)² + 1 = 13

Looks like we will just keep going up.

Now let's try using terms bigger than 6.

Plugging in 7

3(1)² + 1 = 4

Plugging in 8

3(2)² + 1 = 13

We just go up both ways because of the x squared term.

So our smallest value is at x = 6 where we have y = 1.

If we go either direction forever to the right or left the terms to get bigger, where it approaches infinity.

So, 1 will have parentheses as it can be reached and infinity will have parentheses as it is unreachable and goes on forever.

[1,∞)

User Tahagh
by
5.0k points